2006
DOI: 10.1080/13880200600592061
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Some Medicinal Lamiaceae (Labiatae) Species

Abstract: In this study, antioxidant properties of Thymus sipyleus Boiss. subsp. sipyleus var. sipyleus, Teucrium chamaedrys L., Mentha longifolia (L.) Hudson subsp. longifolia, Salvia limbata C.A. Meyer, and Thymus fallax Fisch. & Mey. were investigated. Antioxidant and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities, reducing powers, and the amount of total phenolic compounds of the extracts were studied. The highest antioxidant activity was shown by T. chamaedrys (decoction, IC 50 : 9.2 mg=ml), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 50 publications
2
45
0
2
Order By: Relevance
“…Teucrium chamedrys and T. montanum are very rich in phenolic compounds with very strong biological activity and antioxidative effects (Č anadanović- Brunet et al 2006;Ozgen et al 2006;Gursoy and Tepe 2009;Stanković et al 2010;Stanković et al 2011b). Stankovic et al (2011a) reported that extracts from different Teucrium species caused cytotoxicity and induced apoptosis in human HCT-116 cells (human colon cancer cell line), hence they could be considered suitable natural anticancer products.…”
Section: Discussionmentioning
confidence: 99%
“…Teucrium chamedrys and T. montanum are very rich in phenolic compounds with very strong biological activity and antioxidative effects (Č anadanović- Brunet et al 2006;Ozgen et al 2006;Gursoy and Tepe 2009;Stanković et al 2010;Stanković et al 2011b). Stankovic et al (2011a) reported that extracts from different Teucrium species caused cytotoxicity and induced apoptosis in human HCT-116 cells (human colon cancer cell line), hence they could be considered suitable natural anticancer products.…”
Section: Discussionmentioning
confidence: 99%
“…Various Thymus species are aromatic plants of Mediterranean flora, commonly used as spices, food preservatives, and traditional medicine (Baytop, 1999;Ismaili et al, 2004;Sokmen et al, 2004). Consequently, there are numerous studies on the antioxidant potential of Thymus species growing in various regions of the world (Ismaili et al, 2004;Sokmen et al, 2004;Agbor et al, 2005;Ozgen et al, 2006;Vitalini et al, 2006). Recent reports show that various Thymus and several Ziziphora species have antioxidant potential (Ismaili et al, 2004;Sokmen et al, 2004;Agbor et al, 2005;Salehi et al, 2005;Ghafari et al, 2006;Ozgen et al, 2006;Vitalini et al, 2006).…”
Section: Antioxidant and Dpph Radical Scavenging Activities Of The Exmentioning
confidence: 99%
“…Medicinal plants and herbs are diverse sources of natural antioxidants. Therefore, there is a great interest concerning the antioxidant properties of medicinal plants and herbs (Velioglu et al, 1998;Cakir et al, 2003Cakir et al, , 2006Ismaili et al, 2004;Sokmen et al, 2004;Salehi et al, 2005;Erdemoglu et al, 2006;Ozgen et al, 2006). This study was undertaken to determine the potential antimicrobial, antioxidant, and free radical scavenging activities of the extracts of some Turkish native herbs.…”
Section: Introductionmentioning
confidence: 99%
“…The free radicals in human body develops a great number of pathological states like inflammation, atherosclerosis, stroke, heart disease, diabetes mellitus, multiple sclerosis, cancer, Parkinson's disease, Alzheimer's disease, etc. (Ozgen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%